Safety and Quality Considerations in Transoral Surgery for Neoplastic Disease. (23rd August 2013) - Stoddard, Timothy R.; Haughey, Bruce H.; Holsinger, F. Christopher; Nussenbaum, Brian; Stadler, Michael E.
Abstract : Objectives: 1) Review the importance of quality and patient safety initiatives in surgical care, identifying the specific role that these play in transoral surgical (TOS) procedures. 2) Describe the usefulness of a surgical safety checklist designed for TOS procedures. Methods: Expert opinion, clinical consensus, and a comprehensive literature search were conducted in this project. A systematic review of the literature between 1946 and January 2013 was performed using Pubmed and Medline. Search terms included: quality, patient safety, otolaryngology, head and neck surgery, Surgical checklist, clinical care pathway, transoral laser microsurgery, transoral robotic surgery. Altogether, 200 abstracts were initially reviewed, and 51 studies were selected based on their relevance to the objectives listed above. Results: A comprehensive review of quality and patient safety initiatives in surgical care revealed that clinical care pathways and surgical safety checklists are effective tools in reducing perioperative morbidity, mortality, and cost of care. In otolaryngology‐head and neck surgery, checklists have only been described for endoscopic sinus surgery. A comprehensive, yet usable, surgical quality and safety checklist for TOS procedures was then developed by the authors based on previously successful models from the literature, as well as from expert opinion. Conclusions: Transoral surgery (TOS), including the use of lasers and/or robotics, is an increasingly used and important treatment option for the management of neoplastic diseases of the head and neck. We propose a comprehensive surgical safety checklist that addresses the unique risks and technical requirements of TOS procedures.